STRATEGI BAITUL MAL WAT TAMWIL (BMT) MASLAHAH CAPEM WANGKAL DALAM MENGANTISIPASI KREDIT MACET (Studi Kasus di BMT Maslahah Capem Wangkal Desa Wangkal Kecamatan Gading Kabupaten Probolinggo) - Nuruddin Armanto; Ayu Rizki Sholeha (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Borrowing and lending is one of the economic activities carried out by financial institutions, especially the BMT Maslahah CapemWangkal cooperative, the BMT Maslahah Capem Wangkal cooperative business activities include the provision of credit. BMT cooperative Maslahah Capem Wangkal as a distributor and provider of credit funds for the community that does not always run smoothly, there are times when debtors do not fulfill obligations according to the agreed time (default). The formulation of the problem in this study are: 1) What causes the occurrence of bad credit in Baitul Maal Wat Tamwil Maslahah Wangkal Sub-Branch? and 2) what is the strategy to anticipate customers of Baitul Maal Wat Tamwil Maslahah Wangkal Sub-Branch Office to avoid bad credit? Objective 1) to find out the causes of bad credit in Baitul Maal Wat Tamwil Maslahah Wangkal Sub-Branch and 2) to find out the strategy used by BMT Maslahah Capem Wangkal in anticipating the occurrence of bad credit. Keywords: Bad Credit, Strategy, BMT